EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIMED PAIR SHARE TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK KELAS XI MIPA SMA NEGERI 12 PADANG - Jusrizal, Jusrizal; Trisna, Silvi; Yanti, Iing Rika (Universitas PGRI Sumatera Barat, 2019)
Background of this research is the use of learning model that used by the teacher, it was not interest for the learners. Physics learning process was not able yet became interest the learners until learners’ achievement at XI MIPA SMAN 12 Padang was not optimum yet. Purpose of this research is to know learners’ physics achievement by using cooperative model timed pair share type better than learners’ physics achievement by using scientifc approach at XI MIPA SMA N 12 Padang. Kinds of this research is quasi experiment with posttest only control design. Population of this research is all of learners at XI MIPA SMA N 12 Padang, they were 5 classes. Tecnique of sample collection is cluster random sampling, which is sample has grouped and selected two classes randomly. They were experiment class dan control class. Instrument that used in this research was essay test and observation. Based on result of data analysis, thus it got the average cognitive value in experiment class = 81,75 and control class = 77,54, afektive value in experiment class = 58,95 and control class = 55,39. Both of classes contributed normal and homogen in real level = 0,05. Statistic test that used is uji-t one side. Based on result of calculation, it got th = 1,73 with ttabel = 1,66, because th > ttabel , thus H0 is rejected and H1 is accepted. Therefore, it can be concluded that hypothesis of this research is accepted, students’ physic achievement by using cooperative model timed pair share type better than learners’ physics achievement by using scientifc approach at XI MIPA SMA N 12 Padang.